History and future of industrial crop accessions preserved by CREA-CI in Bologna and Rovigo, Italy - Ilaria Alberti; Manuela Bagatta; Andrea Del Gatto; Massimo Montanari; Daniela Pacifico; Andrea Carboni (Genetic Resources)
The conservation and exploitation of industrial crops at the Cereal and Industrial Crop Centre of the Council for Research in Agriculture and Economics (CREA-CI, the Bologna and Rovigo Research Centres) date back to the beginning of the 20th century and has led to the development of a germplasm bank containing 2,237 accessions. This collection reflects the multidisciplinary approach to the study of these crops and consists of wild relatives, traditional ecotypes and landraces collected in Italy and Europe, breeding lines and populations, as well as ancient and modern varieties. The main crops of this collection are sugar beet (Beta vulgaris L., 381 accessions), flax (Linum usitatissimum L., 283 accessions), hemp (Cannabis sativa L., 90 accessions), potato (Solanum tuberosum L., 45 accessions), sunflower (Helianthus annuus L., 95 accessions), several species of the Brassicales order (75 accessions), castor bean (Ricinus communis L., 18 accessions) and grain legumes (1,250 accessions).This germplasm is maintained according to international standards; most of the accessions are stored in triple-layer vacuum bags and generally kept in two separate locations, at -20° to -25°C and/or in a cold chamber under low temperature (5°C) and low humidity, while the potato collection is maintained in vitro. Each of these crops has been studied using different approaches, including genetic and genomic studies as well as chemical analyses. This article describes the genesis and the evolution of the collection preserved at CREA-CI and how these plant genetic resources are fundamental to facing climate change, and ensuring global food security and environmental sustainability.